'Pretaliatory' Enforcement Action for Chilling Whistleblowing through Corporate Agreements: Lessons from North America. (September 2018) - Dixon, Olivia
Studies have shown that potential whistleblowers are reluctant to report misconduct because they fear retaliation. In Australia, fear of retaliation is exacerbated for private-sector employees where the lack of prescriptive legislation aggravates vulnerability in all but exceptional circumstances. Through examining the codes of conduct of Australia's 100 largest listed companies ('Codes') this article argues that while Codes have the potential to provide an important regulatory function through facilitating whistleblowing, the breadth of confidentiality undertakings contained therein may instead be chilling potential whistleblowers from speaking up. While companies have legitimate interests in protecting confidential information, it is well-established that employees may disclose their employer's unlawful conduct to the government, even if such disclosure is in violation of the company's confidentiality policy. To affirm this right, in the United States (US), federal regulators have recently taken 'pretaliatory' enforcement action against companies for requiring employees to execute confidentiality agreements that stifle the reporting of possible violations of federal laws. Such regulation by enforcement has successfully effected cultural change through facilitating widespread amendments to US corporate confidentiality agreements. Accordingly, this article argues that any future Australian legislation should include an 'anti-confidentiality provision' similar to the US and Canadian frameworks to affirm an employee's right to communicate with a regulator directly, despite any purported agreement or corporate policy to the contrary.